Tindak Pidana Cyberstalking di Media Sosial Menurut Prespektif Hukum Pidana Islam - Ridho Wanantho; Dodi Irawan; Paisol Burlian (Journal of Sharia and Legal Science, 2024)
This study discusses How Cyberstalking Crimes Are on Social Media and discusses How the Perspective of Islamic Criminal Law on Cyberstalking Crimes on Social Media. The purpose of this study is to find out about the sanctions for cyberstalking crimes both in positive criminal law and Islamic criminal law. This study uses normative legal research with a literature review type. The results of this study can be concluded that someone commits a cyberstalking crime on social media by taking actions to disturb, attack, threaten, harass, and force their victims to do something or not do something. By using the internet or technology such as smartphones, computers, or other technologies. With the intention of terrorizing, intimidating, and scaring the victim. Subject to the article on cyberstalking crimes, namely Article 29 of Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). Meanwhile, the punishment for cyberstalking perpetrators according to the perspective of Islamic criminal law is included in the category of ta'zir crimes, where this punishment is determined by the government or local authorities related to freedom (prison sentences and exile) which are of a learning nature to improve the behavior of cyberstalking perpetrators.